2022
DOI: 10.1111/bcp.15530
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the inter‐rater reliability of drug treatment assessments according to the STOPP/START criteria

Abstract: Aims The aim of this study is to revisit the inter‐rater reliability of drug treatment assessments according to the Screening Tool of Older Persons' Prescriptions (STOPP)/Screening Tool to Alert to Right Treatment (START) criteria. Methods Potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) were independently identified by two physicians in two cohorts of older people (I: 200 hip fracture patients, median age 85 years, STOPP/START version 1; II: 302 primary care patients, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…The fact that many PIMs/PPOs were discordantly identified may be regarded as a limitation. This finding is elaborated on in a separate publication . By contrast, early reliability studies of the STOPP/START criteria showed strong to almost perfect interrater identification .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The fact that many PIMs/PPOs were discordantly identified may be regarded as a limitation. This finding is elaborated on in a separate publication . By contrast, early reliability studies of the STOPP/START criteria showed strong to almost perfect interrater identification .…”
Section: Discussionmentioning
confidence: 87%
“…This finding is elaborated on in a separate publication. 35 By contrast, early reliability studies of the STOPP/START criteria showed strong to almost perfect interrater identification. 36,37 Another limitation is that the Swedish set is primarily intended for patients aged 75 years or older, whereas the STOPP/START criteria as well as the EU(7)-PIM list are intended for people 65 years or older.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…Đa bệnh là nguyên nhân chính của việc điều trị bằng nhiều loại thuốc và là yếu tố rủi ro chính dẫn đến việc kê đơn không phù hợp cũng như các phản ứng và các biến cố của thuốc [7]. Việc kê đơn thuốc cho người cao tuổi thường diễn ra trong một môi trường phức tạp liên quan đến sự hiểu biết về tác động của lão hóa đối với sinh lý và dược động học, kiến thức về dược lý, khả năng cân bằng rủi ro so với lợi ích người bệnh; Vì thế, có thể là một thách thức trong quá trình kê đơn ở người cao tuổi, vì đa số bệnh nhân mắc nhiều bệnh lý đồng thời và do đó thường được kê nhiều loại thuốc trong đơn [6], [9]. Gần đây, có một nghiên cứu cho thấy: Trên thế giới có tới 81,5% người >85 tuổi mắc đa bệnh, cao hơn gấp ba lần so với những người 70 tuổi; trong đó, nhóm tuổi 65-74 tuổi chiếm 62% và 50% ở nhóm dưới 65 tuổi.…”
Section: đặT Vấn đềunclassified
“…In the current literature, studies have mainly examined the effect of potentially inappropriate prescribing (PIP) criteria (such as STOPP and Beers) on an older individual’s risk of experiencing an ADE [ 13 – 15 ]. These studies have generally reported the effect at the overall PIP level; though the utility, validity, and clinical relevance of such PIP criteria for real-world clinical practice has been questioned [ 16 , 17 ]. More recently, researchers in the Netherlands published a study describing preventable ADEs caused by three high risk potential DDIs in patients admitted to intensive care units [ 18 ].…”
Section: Introductionmentioning
confidence: 99%